2016
DOI: 10.1038/srep38293
|View full text |Cite
|
Sign up to set email alerts
|

The Disinfection Characteristics of Ebola Virus Outbreak Variants

Abstract: The recent Ebola virus outbreak in West Africa has forced experts to re-evaluate their understanding of how to best disinfect areas contaminated with infectious bodily fluids. Recent research has found that Ebola virus remains viable in blood for 7–10 days making appropriate disinfection crucial to infection control. We sought to determine if the three most important outbreak variants of Zaire ebolavirus (Mayinga, Kikwit and Makona) exhibit separate phenotypes when challenged with a range of sodium hypochlorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
4
28
0
2
Order By: Relevance
“…Summary: Overall, a 15-min exposure to 0.5% chlorine (independently of chlorine type, surface, pre-cleaning practices and organic matter) was found to reduce surface contamination by an Ebola virus surrogate to non-detectable levels. These results are consistent with recent results from small-scale studies using the Ebola virus [18].…”
Section: Evd Research Thread #2: Surface Cleaning Resultssupporting
confidence: 93%
“…Summary: Overall, a 15-min exposure to 0.5% chlorine (independently of chlorine type, surface, pre-cleaning practices and organic matter) was found to reduce surface contamination by an Ebola virus surrogate to non-detectable levels. These results are consistent with recent results from small-scale studies using the Ebola virus [18].…”
Section: Evd Research Thread #2: Surface Cleaning Resultssupporting
confidence: 93%
“…The Vero E6 cultures were inoculated with undiluted neutralized samples and passaged twice. +, viral CPE observed; −, viral CPE not observed, or no cytotoxicity observed for N + NaOCl (neutralizer + NaOCl cytotoxicity control) (modified from Cook et al 11 ). www.nature.com/scientificreports/ log 10 reduction in viral titer on each surface beyond the cytotoxic level. "…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al 11 previously examined the efficacy of 70% ethanol and several concentrations of sodium hypochlorite against three variants of the Ebola virus (Mayinga, Kikwit, and Makona). The authors found that the Makona variant was somewhat less susceptible to the lower concentrations of sodium hypochlorite, while being similarly susceptible to 70% ethanol and higher concentrations of sodium hypochlorite 11 . We therefore expect that the efficacy data obtained here for the Makona variant should apply also to other outbreak variants of Ebola virus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations